Implementasi senam tradisional gemar gatra untuk meningkatkan motorik kasar pada anak tunanetra - Herman Afrian; Wahjoedi Wahjoedi; I Ketut Iwan Swadesi; M. Irsyadul Majdi; M. Zaenul Majdi; M. Rizki Wahyudi; M. Mashuri; Mahendra Mahendra; Mohammad Zulpikri (Jurnal Porkes, 2023)
The problem of this study is the low gross motor skills of blind children at SLBN East Lombok. This study uses the classroom action research method with a process of planning, implementing, observing and reflecting. The population is East Lombok SLBN students with a sample of 21 students, 11 boys and 10 girls. The sampling technique used was purposive sampling, the instruments used were observations and checklists. The analysis technique uses descriptive statistics. The results of the study can improve gross motor skills in children with visual impairments, pre-action activities indicator prefix attitude 55.56% increase 62.97% cycle I, increase 88.89% cycle II, indicators of accuracy in carrying out directed movements mean pre-action average of 44 .44%, increased by 48.14% cycle I, increased by 81.48% cycle II, indicators of skill in performing hand movements, foot movements and verbal commands in pre-action activities averaged 44.44%, increased by 48.14% cycle I , an increase of 77.78% in cycle II, the indicators of hand and foot combination skills in pre-action activities averaged 33.33%, to 40.74% cycle I 77.78% cycle II. The conclusion is that blind SLBN students throughout East Lombok can be improved by providing stimulation of gymnastic movements or traditional games, one of which is through traditional fond gatra gymnastics.